New technologies and human rights : challenges to regulation - Cunha, Mario Viola de Azevedo; Andrade, Norberto Nuno Gomes de; Lixinski, Lucas; Feteira, Lucio Tome (Farnham, Surrey, England : Ashgate, 2013)
'Whilst advances in biotechnology and information technology have undoubtedly resulted in better quality of life for mankind, they can also bring about global problems. The legal response to the challenges caused by the rapid progress of technological change has been slow and the question of how international human rights should be protected and promoted with respect to science and technology remains unexplored. The contributors to this book explore the political discourse and power relations of technological growth and human rights issues between the Global South and the Global North and uncover the different perspectives of both regions. They investigate the conflict between technology and human rights and the perpetuation of inequality and subjection of the South to the North. With emerging economies such as Brazil playing a major role in trade, investment and financial law, the book examines how human rights are affected in Southern countries and identifies significant challenges to reform in the areas of international law and policy'--Provided by publisher.
Privacy, security and new technologies : a Brazilian approach to privacy issues in the public security field / Mario Viola de Azevedo Cunha and Danilo Doneda -- Proposing a right to identity within the international framework of human rights : issues and prospects / Norberto Nuno Gomes de Andrade and Paul De Hert -- Legal implications of the privatization of cyber warfare / Lucas Lixinski -- Internet content filtering in Latin America : reasons and impacts on freedom of expression / Joana Varon Ferraz, Carlos Affonso Pereira de Souza, Bruna Magrani and Walter Britto -- Nanotechnology, human rights, patent law and the global south : a brief overview / Ana Nordberg.
Includes bibliographical references and index.
Keywords: Human rights; Technological innovations -- Law and legislation; Civil rights